THE INFLUENCE OF INTERNAL CONTROL SYSTEM EFFECTIVENESS, COMPENSATION COMPLIANCE, AND INFORMATION ASYMMETRY ON THE TENDENCY OF ACCOUNTING FRAUD (A CASE STUDY ON SEHATI CREDIT UNION) - Amalia Nurul Hidayah; Misdiyono Misdiyono (Universitas Gunadarma, 2019)
A cooperative is a governmental organization established to enhance economic growth and national unity. As the development of the law on cooperatives, the present and developing institutions similar to Savings and Loan Union is called Credit Union. A cooperative is very vulnerable to the risk of loss. Insecurity is possible because of the tendency of accounting fraud. Some things that can affect the tendency of accounting fraud are internal control, compliance compensation, and information asymmetry. This research aims to determine whether there is any influence of internal control system effectiveness, compensation compliance, and information asymmetry on the tendency of accounting fraud. The research uses the quantitative method, and the research subject is Sehati Credit Union. The research data consist of primary and secondary data, especially the purposive sampling data which are collected from 36 respondents. Whereas, the data analysis technique uses multiple regression analysis using SPSS 21 software for Windows. The research concludes that the effectiveness of internal control system has a partially positive significant influence on the tendency of accounting fraud, compensation compliance has a partially negative significant influence on the tendency of accounting fraud, and information asymmetry has a partially positive significant influence on the tendency of accounting fraud. It means that the effectiveness of the internal control system, compensation compliance, and the information asymmetry have significant influences on the tendency of accounting fraud.